Faktor - Faktor Yang Mempengaruhi Perilaku Agen Brilink PT. Bank Rakyat Indonesia (Persero) Tbk Kantor Cabang Bitung - Lelengboto, Jeane Elisabeth (Universitas Sam Ratulangi, 2017)
The purpose of this research is to analyze the factors that influence agent behavior that is culture, social, personality, and psychological at BRILink agent PT Bank Rakyat Indonesia (Persero) Tbk Bitung Branch Office. The type of research conducted in this study is quantitative research. Population in this research is all BRILink agent in PT. Bank Rakyat Indonesia (Persero) Tbk in Bitung Branch Office. The data were collected by purposive sampling. The questionnaire distributed is 100. The data analysis method used in this research is using factor analysis technique. The results showed that factors considered in the behavior of BRILink agents PT. Bank Rakyat Indonesia (Persero) Tbk Branch Office Bitung is the behavior of cultural lifestyle, socio-cultural environment, agency decisions, personal, social statusKeywords: Culture, Social, Personality, Psychological